2022
DOI: 10.1002/adfm.202207849
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of H2 and O2 Recombination: The Key to a Most Efficient Single‐Atom Co‐Catalyst for Photocatalytic H2 Evolution from Plain Water

Abstract: In the present work, it is shown that anodic TiO 2 nanotubes (NTs) can be decorated with Pt, Pd, Rh, and Au single atoms (SAs) by a simple "dark deposition" approach. Such TiO 2 NTs with surface trapped noble metal SAs provide a high activity for photocatalytic H 2 generation from pure water, i.e., in absence of a sacrificial agent. However, noble metals also act as active centers in the undesired hydrogen back-oxidation (H 2 + O 2 → H 2 O), leading to a decrease in the overall photocatalytic H 2 production ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 93 publications
1
16
0
Order By: Relevance
“…In photocatalytic H 2 production, TiO 2 needs to be decorated with a suitable co-catalyst such as Pt. 11,12 As such, TiO 2 has sufficient surface oxo groups for SA-trapping. 13−16 However, it is still challenging to stabilize many noble metals as SAs on TiO 2 surfaces because of the relatively weak bonding between oxo groups and most noble metal SAs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In photocatalytic H 2 production, TiO 2 needs to be decorated with a suitable co-catalyst such as Pt. 11,12 As such, TiO 2 has sufficient surface oxo groups for SA-trapping. 13−16 However, it is still challenging to stabilize many noble metals as SAs on TiO 2 surfaces because of the relatively weak bonding between oxo groups and most noble metal SAs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…TiO 2 , as one of the most mature semiconductor materials, has the advantages of stability, cheapness, and environmentally friendly and is also a potential support for anchoring SAs. [68] Introducing defects in TiO 2 can improve the stability and activity of SACs. [33,[69][70][71] TiO 2 with oxygen-vacancy-rich defects exhibited superior photocatalytic hydrogen production and CO 2 reduction performance than original TiO 2 at the same Pt SAs loading.…”
Section: Metal Oxides/sulfidesmentioning
confidence: 99%
“…Interestingly, it has been reported that noble metal co-catalysts can catalyze the backward reaction between H 2 and O 2 . However, when noble metals are present in the form of single atoms, they hinder this recombination process, thus potentially improving the overall efficiency of water splitting …”
Section: Introductionmentioning
confidence: 99%
“…However, when noble metals are present in the form of single atoms, they hinder this recombination process, thus potentially improving the overall efficiency of water splitting. 14 Various methods have been proposed to synthesize SACs, including bath deposition, vapor deposition, atomic layer deposition (ALD), 15−17 co-precipitation, 18,19 and wet-chemical synthesis such as impregnation and photo deposition. 20−22 A promising and straightforward strategy for anchoring single atoms (SAs) onto suitable support materials involves nanoand atomic-scale defect engineering.…”
Section: Introductionmentioning
confidence: 99%